Renaissance art, music & literature - Schlessinger, Andrew; V. Dennett, Ashleigh; Schlessinger Media; Tremendous Entertainment (Wynnewood, PA : Schlessinger Media, 2004)
Explores the newly discovered uses of realism, mathematics and perspective in art, the introduction of new musical instruments and changes in musical style, and how literature flourished thanks to the invention of the printing press
Teacher's guide and other resources on this topic are available online
Grades 5-9
Executive producer, Andrew Schlessinger ; produced and directed by, Ashleigh V. Dennett ; writer, Dave Rodrich ; edited by, Jay Gallentine, Angela Heins
Keywords: Art, Renaissance; Art -- 15th century; Art -- 16th century; Music -- History; European literature